Description of Myxacorys almedinensis sp. nov. (Synechococcales, Cyanobacteria) isolated from the limestone walls of the Old Cathedral of Coimbra, Portugal (UNESCO World Heritage Site) - Soares, Fabiana; Tiago, Igor; Trovão, João; Coelho, Catarina; Mesquita, Nuno; Gil, Francisco; Catarino, Lídia; Cardoso, Susana M.; Portugal, António (Phytotaxa, 2019)
Cyanobacteria are photoautotrophic microorganisms able to colonize historic stone monuments, causing severe aesthetic, physical and chemical alterations to the substrate. In a study that aimed to fingerprint the phototrophic community of the biodeteriorated walls of the Old Cathedral of Coimbra (UNESCO World Heritage Site), an unknown Myxacorys-like cyanobacterium was isolated. In this paper, we employed a polyphasic approach based on morphological, ecological and phylogenetic analyses of the partial 16S and the whole 16S-23S ITS rRNA regions. The resulting analyses allowed us to propose the description of a new species, Myxacorys almedinensis sp. nov. within the genus Myxacorys.